2012
DOI: 10.1136/annrheumdis-2012-201508
|View full text |Cite
|
Sign up to set email alerts
|

Steroid injection for inferior heel pain: a randomised controlled trial

Abstract: In this study, steroid injection showed a clear benefit over placebo at 6 weeks and this difference was maintained at 12 weeks. Trial Registration No ISRCTN79628180 (www.controlled-trials.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 36 publications
8
92
0
1
Order By: Relevance
“…In corticosteroid injection group, Mean BMI was 27.6 while In autologous blood injection group, Mean BMI was 28.46 (p value = 0.47). Similar studies conducted by Modi et al [12] , Abdihakin et al [13] and Ball et al [16] favoured obesity and over-weight as a predisposing factor . Pre-injection Mean VAS score for two groups was 7.60 and 7.33 respectively (p value 0.225, not significant, hence comparable)( Table 2).…”
Section: Resultssupporting
confidence: 82%
“…In corticosteroid injection group, Mean BMI was 27.6 while In autologous blood injection group, Mean BMI was 28.46 (p value = 0.47). Similar studies conducted by Modi et al [12] , Abdihakin et al [13] and Ball et al [16] favoured obesity and over-weight as a predisposing factor . Pre-injection Mean VAS score for two groups was 7.60 and 7.33 respectively (p value 0.225, not significant, hence comparable)( Table 2).…”
Section: Resultssupporting
confidence: 82%
“…All of the included studies compared corticosteroid injection and placebo injection in the treatment of plantar fasciitis. Two studies were performed in UK (7,10), one in Australia (8) and one in Kenya (9). The patients in the included studies were middle-aged and elderly, with an average age of between 43.1 and 58.2 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…At present, several published randomized controlled trials (RCTs) (7)(8)(9)(10) have compared the efficacy of corticosteroid injection with that of placebo injection for the management of plantar fasciitis; however, the efficacy of corticosteroid injection remains controversial. The present meta-analysis was performed to determine the efficacy of corticosteroid versus placebo injection for the treatment of plantar fasciitis.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled study involving 106 patients, Crawford et al [21] reported that CS injections were superior to placebo at 1 month, but not at subse- PAIN A RI quent follow-up assessments. In another randomized study, Ball et al [22] reported that CS injection had short-and medium-term benefits in a study involving 65 patients with plantar fasciitis. We observed a significant improvement in pain in 10 patients with plantar fasciitis after CS injections.…”
Section: Discussionmentioning
confidence: 99%
“…CS injections for plantar fasciitis are known to be an effective choice of treatment. [20][21][22][23][24] In a study by Li et al, [20] treatment with steroid injections had-a significant effect only at the 1-month, and not the 6-or 12-month, follow-ups. In a randomized controlled study involving 106 patients, Crawford et al [21] reported that CS injections were superior to placebo at 1 month, but not at subse- PAIN A RI quent follow-up assessments.…”
Section: Discussionmentioning
confidence: 99%